The New Encyclopaedia Britannica in 32 volumes. (Chicago : Encyclopaedia Britannica, 2007)
[1] Propaedia: outline of knowledge and guide to the Britannica.--[2] Micropaedia: ready reference and index. 12 v.--[3] Macropaedia: knowledge in depth. 19 v.
The Micropaedia is numbered v. 1-12. Includes bibliographies and index.
Keywords: Encyclopedias and dictionaries